Personal Branding Strategy of Food Vlogger Serly Ansim Through TikTok Account @onebitebigbite - Elvita Octavia Br Surbakti; Syafrida Nurrachmi Febriyanti (Lavish Opulent Education, 2025)
The rapid development of social media, particularly TikTok, has created new opportunities for content creators to build their personal image through fast, creative, and easily accessible visual content. One emerging phenomenon is the increasing number of food vloggers who use TikTok as a medium for developing personal branding. This study aims to examine the personal branding strategy employed by Serly Ansim through her TikTok account @onebitebigbite, known for her humorous, expressive, and bold characteristics. Using a qualitative approach with Krippendorff’s content analysis method, the study is based on non-participant observation of 12 videos with the highest engagement from March to August 2025, supported by audience comments and relevant literature. The findings reveal that Serly Ansim’s personal branding is constructed through three key characteristics proposed by McNally & Speak (2004): (1) Distinctiveness, reflected in her spontaneous and humorous communication style, signature expressions such as “DAR DER DOR,” dynamic and detailed visuals, and strong storytelling techniques; (2) Relevancy, shown through her ability to adapt content to TikTok trends, audience culinary preferences, viral moments, and relatable humor for younger viewers; and (3) Consistency, demonstrated through a stable tone of voice, presentation style, video format, and commitment to honest food reviewers. These three aspects have enabled Serly Ansim to build a strong personal brand, increase audience trust, and position herself as a prominent food vlogger on TikTok. This study is expected to contribute theoretically to the study of personal branding in new media and serve as a practical reference for content creators, creative industry practitioners, and food vloggers in developing effective digital communication strategies.